2011
DOI: 10.1186/1471-230x-11-40
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and constipation in adolescents

Abstract: BackgroundThe association between overweight and gastrointestinal symptoms has been recently studied in the literature; however, few studies have evaluated the association between overweight and constipation in adolescents in a community-based sample. The aim of this study was to analyze the prevalence of constipation and its association with being overweight in a community-based survey with adolescents.MethodsThis cross-sectional study included 1,077 adolescents who were enrolled in five schools in the city o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 22 publications
4
28
1
4
Order By: Relevance
“…In our study, 6.8% of girls and 2.7% of boys developed constipation during the 3-year period (female OR 2.62, Table 2), which seemed comparable to the results of many cross-sectional studies showing that female adults are more likely to be constipated than male adults, although sex differences in the prevalence of constipation among children have been inconsistent [1,2,19,20 ]. Some mechanisms of female predominance in constipation have been demonstrated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, 6.8% of girls and 2.7% of boys developed constipation during the 3-year period (female OR 2.62, Table 2), which seemed comparable to the results of many cross-sectional studies showing that female adults are more likely to be constipated than male adults, although sex differences in the prevalence of constipation among children have been inconsistent [1,2,19,20 ]. Some mechanisms of female predominance in constipation have been demonstrated.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies conducted in clinical settings showed that children with functional constipation had a higher prevalence of obesity than controls [24,25]. Meanwhile, most previous population-based studies for healthy children reported no association [20,26] or an inverse association between obesity and constipation [7,[25][26]. In our study, children who were overweight were less likely to develop constipation.…”
Section: Discussioncontrasting
confidence: 47%
“…These measurements compared to the 2000 Centers for Disease Control and Prevention (CDC) growth chart of BMI for children aged 2 to 20 years. 2 Subjects with BMI ≥ 95 th percentile were classified as obese; those with BMI between 5t h percentile and < 85 th percentile were classified as normoweight children.…”
Section: Methodsmentioning
confidence: 99%
“…1 Most studies on a correlation between obesity and functional constipation have been done in developed countries. 2 Obese children usually consume a low fiber diet and engage in less physical activity than normoweight children. These two factors result in altered defecation patterns.…”
mentioning
confidence: 99%
“…Older and less educated individuals suffering from constipation might also tend to be overweight (Pourhoseingholi et al ., ). However, in general, constipation would not be linked to obesity (Costa et al ., ; Eslick, ).…”
Section: Background Information On Constipationmentioning
confidence: 99%